Odpowiedzi

2010-03-24T21:08:54+01:00
⅚(y-4)-⅓=¼(y+5)+½

⅚y-10/3-⅓=¼y+5/4+½

⅚y-¼y=5/4+½+10/3+⅓

10/12y-3/12y=15/12+6/12+40/12+4/12

7/12y=65/12 /*(razy) 12/7

y=65/7=9całych2/7
2010-03-24T21:10:17+01:00
⅚(y-4)-⅓=¼(y+5)+½
5/6y-10/3-1/3=1/4y+5/4+1/2
5/6y-11/3-1/4y=5/4+2/4
10/12y-3/12y=7/4+11/3
7/12y=21/12+44/12
7/12y=65/12 *12/7
y=65/7=9 2/7
2010-03-24T21:13:03+01:00
⅚(y-4)-⅓=¼(y+5)+½

5/6y-10/3-1/3 = 1/4y+5/4+1/2
10/12y-3/12y-11/3 = 5/4+2/4
7/12y = 11/3+7/4
7/12y = 44/12+21/12
7/12y = 65/12 /*12
7y = 65 /7
y = 65/7
to w przybliżeniu 9,3